The Influence of E-Service Quality and Brand Trust on Repurchase Intention of Luxcrime Products on Shopee E-Commerce - Fania, Salsa; Rachmawati, Mariana (DINASTI RESEARCH, 2025)
The purpose of this study is to examine the influence of e-service quality and brand trust on repurchase intention of Luxcrime products on the Shopee e-commerce platform. The object of this study is the Luxcrime Official Store on Shopee, with the observation unit being consumers who shop at the store. E-Service Quality has a positive and significant effect on Repurchase Intention, proving that a fast, easy, and responsive digital service experience plays an important role in shaping consumer loyalty. The better the service quality perceived by consumers, the higher the likelihood they will repurchase Luxcrime products through Shopee. Brand Trust has a positive and significant effect on Repurchase Intention. Consumer trust in the quality, reputation, and consistency of the Luxcrime brand is a crucial factor in shaping repurchase decisions. This trust strengthens positive perceptions and reduces doubts about the risks of purchasing beauty products online. E-Service Quality and Brand Trust on Repurchase Intention: Simultaneously, E-Service Quality and Brand Trust have a very significant influence on Repurchase Intention, this emphasizes the importance of an integrated strategy in managing digital service quality and strengthening brand identity to maintain customer loyalty on e-commerce platforms.